ANALISIS WILAYAH KOMODITAS KOPI DI INDONESIA - Ati Kusmiati; Reni Windiarti (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2011)
This research was intended (1) to map areas of coffee production and land base in Indonesia, (2) to identify the characteristics of the coffee commodity distribution in Indonesia, (3) to identify the roles of coffee in supporting plantation sector in Indonesia. The research area was determined by using purposive method, research was conducted in Indonesia. The method used in this research was descriptive and analytical method. The data used were secondary data in the periods of 2009-2018. Methods of data analysis used were analysis (LQ), analysis of localization and specialization, analysis of Basic Service Ratio (BSR) and Regional Multiplier (RM). The research results showed that: (1) Areas of coffee production bases consisted of: Nanggroe Aceh Darussalam, South Sumatra, Bengkulu, Lampung, East Java, Bali, West Nusa Tenggara East Nusa Tenggara and South Sulawesi. Areas of coffee commodity bases based on indicators such as land size were Nanggroe Aceh Darussalam, West Sumatera, South Sumatera, Bengkulu, Lampung, East Java, Bali, East Nusa Tenggara and South Sulawesi; (2) Characteristics of the spread of coffee did not lead to the principles of localization and specialization; (3) Coffee commodity was capable of supporting the activities of plantations in Indonesia.Keyword: Areas of coffee production and land bases, localization and specialization, Basic Service Ratio, Regional Multiplier